PEDAGOGI NIR-KEKERASAN DALAM PANDANGAN MOHANDAS KARAMCHAND GANDHI DAN RELEVANSINYA BAGI PENGEMBANGAN PENDIDIKAN KARAKTER - Gede Agus Siswadi; I Dewa Ayu Puspadewi (Jawa Dwipa, 2025)
This research examines the concept of non-violent pedagogy in the view of Mohandas Karamchand Gandhi and its relevance for the development of character education. Gandhi viewed non-violent pedagogy as an essential foundation in building individuals who are not only intellectually intelligent, but also have high morality. This concept emphasises the importance of education as a means to strengthen human values, such as honesty, justice and empathy. This research uses a descriptive-analytical approach by analysing Gandhi’s writings and thoughts on education and non-violence. The results of this study show that Mohandas Karamchand Gandhi's thoughts have a deep relevance to the development of character education, especially in the context of moral and spiritual values. One of Gandhi's main contributions is the concept of non-violent pedagogy or ahimsa, which emphasises the rejection of violence in all its forms. Gandhi also taught the concepts of satyagraha, aparigraha, brahmacarya, asteya, and swadesi, a concept that directs individuals to always serve the truth, then become a simple individual and not too pursue luxury, always control themselves, do not take the property of others, and also teach the principle of independence.